The Validity of the Muqaran Interpretation Method in the Contemporary Era - Fikri Fillaili; Hasan Subhani; Eni Zulaiha (al-Afkar, Journal For Islamic Studies, 2026)
Muqaran interpretation emerged as a method of interpreting the Qur'an that focuses on comparing various scholars' views on specific verses. Its emergence was driven by the need to understand and respond to differences in interpretation across both classical and modern traditions. The foundation and urgency of this method lie in its ability to broaden interpretive perspectives, foster tolerance towards differing opinions, and avoid sectarianism. This method emphasizes objectivity in understanding Qur'anic texts by considering diverse perspectives from past and contemporary scholars. The steps of the Muqaran method involve identifying relevant verses or themes, collecting various scholarly opinions, conducting a comparative analysis, and synthesizing deeper meanings. Muqaran exegesis compares similar or related Qur'anic verses, seemingly contradictory hadiths, and classical and contemporary scholarly views. Its strengths include broadening perspectives and promoting tolerance, while its weaknesses lie in overemphasis on comparison and less direct social solutions. In the contemporary era, the Muqaran method remains valid through approaches of coherence, correspondence, and pragmatism, providing answers to modern challenges and contributing contextually to social, cultural, and political problem-solving.